Gen Transfer in Cultivation Shrimp Commodity - Jacinda, Adinda Kinasih; Yustiati, Ayi (Torani Journal of Fisheries and Marine Science, 2021)
GMO is a product of biotechnology through genetic engineering techniques. This can be done to increase food availability and reduce production costs, especially by manipulating the genes and chromosomes of cultivated species. In invertebrates such as shrimp, the application of gene transfer is still limited to the recognition and expression of foreign genes and focuses on increasing disease resistance. Among several gene transfer methods (microinjection, electroporation and transfection), transfection method is the most effective method to be applied to shrimp. It is characterized by high hatching data and is not toxic. In addition, the use of GMO in aquaculture is a highly controversial issue due to many environmental and health issues. This journal will discuss gene manipulation by means of gene transfer to improve shrimp culture.